2019
DOI: 10.2147/jir.s190007
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pro-inflammatory agents released by pathogens, dying host cells, and neutrophils act synergistically to destroy host tissues: a working hypothesis</p>

Abstract: We postulate that the extensive cell and tissue damage inflicted by many infectious, inflammatory and post-inflammatory episodes is an enled result of a synergism among the invading microbial agents, host neutrophils and dead and dying cells in the nidus. Microbial toxins and other metabolites along with the plethora of pro-inflammatory agents released from activated neutrophils massively recruited to the infectious sites and high levels of cationic histones, other cationic peptides, proteinases and Th1 cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Pathogenic bacteria are causative agents for a wide spectrum of infectious diseases. Bacterial infection causes tissue damage through different mechanisms, including the killing of infected host cells, the secretion of toxins and the induction of an exacerbated inflammatory response [21]. In vivo studies demonstrated that CD38 deficiency in mice conferred increased susceptibility to infection by several bacteria, namely Listeria monocytogenes (L. monocytogenes) [22], Mycobacterium avium (M. avium) [23] and Streptococcus pneumoniae (S. pneumoniae) [24,25], and the parasite Entamoeba histolytica (E. histolytica) [26].…”
Section: Cd38 Deficiency Results In Increased Susceptibility To Severmentioning
confidence: 99%
“…Pathogenic bacteria are causative agents for a wide spectrum of infectious diseases. Bacterial infection causes tissue damage through different mechanisms, including the killing of infected host cells, the secretion of toxins and the induction of an exacerbated inflammatory response [21]. In vivo studies demonstrated that CD38 deficiency in mice conferred increased susceptibility to infection by several bacteria, namely Listeria monocytogenes (L. monocytogenes) [22], Mycobacterium avium (M. avium) [23] and Streptococcus pneumoniae (S. pneumoniae) [24,25], and the parasite Entamoeba histolytica (E. histolytica) [26].…”
Section: Cd38 Deficiency Results In Increased Susceptibility To Severmentioning
confidence: 99%
“…UC and CD share some risk factors, such as age, smoking habits, appendicitis, autoimmune diseases, diet, lifestyle and genetics [33]. The NOD2 gene has been associated with IBD, whose genetic variants are associated with increased susceptibility to the development of CD [34].…”
Section: Nets In Inflammatory Bowel Diseasementioning
confidence: 99%
“…UC is an inflammatory bowel disease that occurs gradually or suddenly in the digestive tract; it damages the lining of the colon and rectum, and it affects the mucosa; it is characterized by the presence of a granular mucosa, superficial ulcers, pseudopolyps, diarrhea, abdominal cramps, fever and fatigue, which can cause friability of the mucosa and bleeding from the intestine [33,36]. With regard to CD, the signs are similar; however, the pathology leads to the development of aphthoid ulcers, fistulas, fissures and stenosis [37].…”
Section: Nets In Inflammatory Bowel Diseasementioning
confidence: 99%
“…These include reactive oxygen and nitrogen species, cationic proteinases, and the membrane-damaging phospholipases and lysophosphatides, 22 – 36 besides the toxic products released by dying cells. 37 It is also of great interest to note that the mechanisms by which PMNs and macrophages destroy tissues are very similar to those mediated by group A haemolytic streptococci. 38 …”
Section: A Novel Working Hypothesis Is Proposed To Explain Mechanisms Governing Ra Pathogenicitymentioning
confidence: 99%